Identifikasi Kelimpahan Dan Karakteristik Fisik Mikroplastik Pada Air Irigasi Sawah Sekitar TPA - Putri, Winda Yunita; Sari, Gina Lova; Amanah, Nadia (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Microplastics have now become one of the most prominent environmental pollutants, particularly due to their impact on aquatic ecosystems and irrigated rice fields. This study aims to identify the abundance and physical characteristics of microplastics in irrigation water from rice fields surrounding the Final Waste Disposal Jalupang, Karawang. Water samples were collected from seven irrigation points using a purposive sampling method and analyzed under a binocular microscope. The results showed the highest microplastic concentration occurred at the primary irrigation inlet, reaching 536.50 particles/L. The predominant shape was fragments, with the majority of particles measuring less than 1.00 mm in size. In terms of color, black and transparent microplastics were the most prevalent, indicating advanced degradation due to prolonged exposure to open environmental conditions. The distribution pattern of microplastics was strongly influenced by the existing condition of the irrigation channels, agricultural activities, and the hydraulic residence time within the paddies. The findings of this study are consistent with previous research indicating that the primary source of microplastics in agricultural land originates from the breakdown of household and agricultural plastic waste, undergoing photodegradation and physical weathering. This study highlights the urgent need for improved plastic waste management and the implementation of sustainable irrigation systems to mitigate microplastic accumulation in agricultural soils.